Addressing 21st Century Communication Skills: Some Emerging Issues from Eil Pedagogy & Intercultural Communicative Competence - Athriyana Santye PATTIWAEL (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2016)
ABSTRACT 21st Century Skills has attracted the attention of various education experts, practitioners, school management, teachers and educational managers in ASEAN countries, including Indonesia. A number of activities in terms of seminars and workshops have been held by a wide range of institutions to address this framework in terms of how to align it to the curriculum and how to integrate it into classroom activities. Regarding communication skills, Partnership for 21st Century Skills defines 21st Century Communication Skills – among the other five definitions – as communicating effectively in diverse environments (including multilingual and multicultural). Realizing that this framework was developed in the American context for their national education purposes, it is imperative for various parties, including teachers and practitioners of English as a Foreign Language, to contextualize it by considering both local and regional contexts. As a minute contribution to the effort of contextualizing the framework, this paper will address some emerging issues in developing the instructional materials framed by the pedagogy of English as an International Language and Intercultural Communicative Competence. ABSTRAK Keterampilan Abad ke-21 telah menarik perhatian beragam kalangan dari pakar pendidikan, praktisi, pengelola sekolah, guru sampai para manajer institusi pendidikan di negara-negara ASEAN, termasuk Indonesia. Serangkaian kegiatan termasuk seminar dan workshop telah diselenggarakan oleh berbagai institusi untuk membedah kerangka kerja ini dalam hal Tentang keterampilan berkomunikasi, Partnership for 21st Century Skills mendefinisikan keterampilan Komunikasi Abad ke-21 -di antara lima definisi lainnya– sebagai kemampuan berkomunikasi secara efektif di berbagai lingkungan (termasuk multibahasa dan multikultural). Menyadari bahwa kerangka kerja ini dikembangkan dalam konteks Amerika untuk tujuan pendidikan nasional mereka, maka sangatlah penting bagi berbagai pihak, termasuk guru dan praktisi bahasa Inggris sebagai bahasa asing, untuk mengkontekstualisasikannya dengan mempertimbangkan konteks lokal dan regional. Sebagai kontribusi kecil terhadap upaya kontekstualisasi tersebut, tulisan ini akan membahas beberapa isu yang muncul dalam pengembangan bahan ajar yang dibingkai oleh pedagogi Bahasa Inggris sebagai Bahasa Internasional dan Kompetensi Komunikasi Antar-budaya. How to Cite: Pattiwael, A., S. (2016). Addressing 21st Century Communication Skills: Some Emerging Issues from Eil Pedagogy & Intercultural Communicative Competence. IJEE (Indonesian Journal of English Education), 3(2), 158-170 doi:10.15408/ijee.v3i2.3164. Permalink/DOI: http://dx.doi.org/10.15408/ijee.v3i2.3164